The Role of Academic Resilience, Motivational Intensity and Their Relationship in EFL Learners' Academic Achievement - Yang, Shengli; Wang, Weirong (Frontiers in Psychology, 2022)
The aim of developing academic resilience and motivational intensity, as two constructs of positive psychology, is to increase learners’ capability to compete with each other even in adverse conditions. Different types of academic resilience are conceptualized and germane literature about the relationship between academic resilience and academic achievement is provided. Literature showed that some socio-affective factors (e.g. peer relations, parents’ high expectations, teachers’ attention, and kindness, etc.), socio-economic factors (e.g. the financial contribution of parents’ to education, economic and social class level, etc.), and affective factors (e.g. anxiety, self-efficacy, motivation and so on) can influence learners’ academic achievement and policy makers’ decision in providing an appropriate context for learning. In the end, the pedagogical implications are expounded to foster the language learning quality, to develop a language educational system. Suggestions for further research are provided to develop the existent literature on the relationship between academic, motivational intensity, and learners’ academic achievement.